Mediatized Da’wah: Muhammadiyah’s Digital Transformation through YouTube @MChannel1912 - Hasibuan, Muhtadiah; Sikumbang, Ahmad Tamrin; Madya, Efi Brata (LPPM IAIN Parepare, 2025)
The swift proliferation of digital media has altered the domain of Islamic preaching, transitioning da’wah from conventional religious venues to algorithmically influenced platforms that redefine the construction and negotiation of religious authority. This paper investigates how Muhammadiyah used @Mchannel1912 YouTube as a platform for mediatized da’wah, focusing on the reconfiguration of religious authority within the digital public realm. This study seeks to examine the techniques, obstacles, and ramifications of Muhammadiyah's digital involvement, emphasising the adaptation of institutional religious communication to media logic while preserving doctrinal integrity. This study utilises a qualitative methodology, including netnography, content analysis of specific YouTube videos, and comprehensive interviews with principal participants in digital da’wah creation. The analysis of data employed an interactive methodology of coding, categorisation, and interpretation, informed by the theoretical framework of mediatization of religion and digital religious communication. The findings indicate that Muhammadiyah’s YouTube strategy exemplifies a degree of partial mediatization, marked by the use of digital production processes while not entirely embracing interactive and algorithm-driven communication methods. This study theoretically enhances the literature on the mediatization of religion by introducing the idea of